2005
DOI: 10.1152/ajpheart.00407.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of β-myosin heavy chain isoform expression on cross-bridge cycling kinetics

Abstract: Myosin heavy chain (MHC) isoforms alpha and beta have intrinsically different ATP hydrolysis activities (ATPase) and therefore cross-bridge cycling rates in solution. There is considerable evidence of altered MHC expression in rodent cardiac disease models; however, the effect of incremental beta-MHC expression over a wide range on the rate of high-strain, isometric cross-bridge cycling is yet to be ascertained. We treated male rats with 6-propyl-2-thiouracil (PTU; 0.8 g/l in drinking water) for short interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
141
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(176 citation statements)
references
References 39 publications
32
141
3
Order By: Relevance
“…Likewise, the impact of variable cTnI PKA phosphorylation was accounted for by the phospho-mimetic cTnI containing troponin exchange procedure, resulting in ϳ93% troponin replacement. Finally, the partial expression of ␤-myosin in the AAA group is unlikely to affect the results of the present study, as no impact on myofilament Ca 2ϩ has been observed upon the complete replacement of ␣-myosin with ␤-myosin in rat myocardium (36,37).…”
Section: Methodsmentioning
confidence: 64%
“…Likewise, the impact of variable cTnI PKA phosphorylation was accounted for by the phospho-mimetic cTnI containing troponin exchange procedure, resulting in ϳ93% troponin replacement. Finally, the partial expression of ␤-myosin in the AAA group is unlikely to affect the results of the present study, as no impact on myofilament Ca 2ϩ has been observed upon the complete replacement of ␣-myosin with ␤-myosin in rat myocardium (36,37).…”
Section: Methodsmentioning
confidence: 64%
“…An altered distribution of MHC isoforms has been shown in myocardial remodelling, cardiac hypertrophy and cardiomyopathy [17,[28][29][30][31], indicating that the regulation of cardiac contractile function is directly related to the relative amounts of MHC-α and MHC-β isozymes [25]. Even a small shift in the relative expression of these isoforms may significantly alter cardiomyocyte power output [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the predominant MHC isoform in healthy human hearts is β rather than α, overexpression of MHC-β in transgenic mice suggests that such an MHC-α to MHC-β switch is a maladaptive response to preserve energy [30]. The MHC isozyme switch from the fast type α isoform to the slow type β isoform (lower ratio of MHC-α to MHC-β) is believed to play a significant role in cardiac dysfunction in diabetes, cardiac hypertrophy and senescence [28,29,49,50]. This is supported by the fact that an increase in MHC-α and a decrease in MHC-β mRNA expression (increased ratio of MHC-α to MHC-β) is deemed beneficial in the improvement of left ventricular function in patients with idiopathic dilated cardiomyopathy [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange of Recombinant Cardiac cTn into Skinned Rat Trabeculae-Free running, unbranched right ventricular trabeculae were dissected from male Lewis Brown Norway-F1 rats (ϳ14 weeks of age; Harlan Laboratories) and, after extraction with Triton X-100, attached to aluminum T-clips (18,19). Exogenous Tn was exchanged for endogenous Tn by slight modification of previously described methods (18).…”
Section: Methodsmentioning
confidence: 99%